2018
DOI: 10.5812/modernc.81084
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Major Congenital Anomalies Among Live Births in Birjand, Iran

Abstract: Background and Objectives: Congenital anomalies can increase the neonatal mortality rate. Infants with anomalies suffer from long-term disabilities that impose heavy burdens on their families and healthcare systems. Understanding the prevalence of congenital anomalies helps health policy-makers develop better health-related policies. This study aimed to evaluate the prevalence of major congenital anomalies among live births in Birjand city, Iran. Methods: This cross-sectional descriptive-analytical study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This is in agreement with Ameen et al, 2018 [26] who found that previous congenital anomalies were associated with high risk of congenital anomalies. This is against Faal et al, 2018 [36] who found that only one affected case was associated with positive family history of congenital anomalies. This study also found that the CA were signi cantly common with urban than rural area.…”
Section: Resultsmentioning
confidence: 75%
“…This is in agreement with Ameen et al, 2018 [26] who found that previous congenital anomalies were associated with high risk of congenital anomalies. This is against Faal et al, 2018 [36] who found that only one affected case was associated with positive family history of congenital anomalies. This study also found that the CA were signi cantly common with urban than rural area.…”
Section: Resultsmentioning
confidence: 75%
“…Another study indicated that the prevalence rates of low birth weight and premature birth were significantly greater among infants with CAs than in their non-afflicted counterparts [ 35 ]. In agreement with previous studies, the result of the present study indicated that 47.6% of the neonates with CAs were preterm (premature) births where a statistically significant difference was observed between the cases and controls, indicating that the occurrence of CAs contributes to premature delivery with low birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Rate of admission to NICU among live born fetuses was found to be 92.8%. Previous studies demonstrated the rate of congenital abnormalities in patients hospitalized at NICU ranging between 13.7 and 48% (Eventov‐Friedman, Kanevsky, & Bar‐Oz, ; Faal, Abbasi, & Bijari, ). Cooperation with other proficiencies and utilization of NICU for patients with congenital abnormality is critical for decreasing mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%